Prospects for Epigenetic Targeted Therapies of Bone and Soft-Tissue Sarcomas. (26th July 2021) - Wang, Jun; Elkrief, Arielle; Guo, Wei; Shukla, Neerav; Gounder, Mrinal; Ladanyi, Marc
Abstract : Targeted therapies have revolutionized cancer treatment. It is well established that alterations of chromatin configuration and modifications affect tumorigenesis of some, possibly most, bone and soft-tissue sarcomas. As epigenetic regulators play a major role in the development of bone and soft-tissue sarcomas, epigenetic drugs provide a novel potential avenue for rational targeted therapies for these aggressive cancers. The present review summarizes the application of epigenetic drugs for clinical utilization in bone and soft-tissue sarcomas and provides an overview of clinical trials currently evaluating epigenetic therapies in this space.